PET/CT in nononcological lung diseases: current applications and future perspectives. (September 2016) - Capitanio, Selene; Nordin, Abdul Jalil; Noraini, Abdul Rahim; Rossetti, Claudio
Positron emission tomography (PET) combined with computed tomography (CT) is an established diagnostic modality that has become an essential imaging tool in oncological practice. However, thanks to its noninvasive nature and its capability to provide physiological information, the main applications of this technique have significantly expanded. 18 F-labelled fluorodeoxyglucose (FDG) is the most commonly used radiopharmaceutical for PET scanning and demonstrates metabolic activity in various tissues. Since activated inflammatory cells, like malignant cells, predominantly metabolise glucose as a source of energy and increase expression of glucose transporters when activated, FDG-PET/CT can be successfully used to detect and monitor a variety of lung diseases, such as infections and several inflammatory conditions. The added value of FDG-PET/CT as a molecular imaging technique relies on its capability to identify disease in very early stages, long before the appearance of structural changes detectable by conventional imaging. Furthermore, by detecting the active phase of infectious or inflammatory processes, disease progression and treatment efficacy can be monitored. This review will focus on the clinical use of FDG-PET/CT in nonmalignant pulmonary diseases. PET/CT is an imaging modality that could play a role in evaluation of inflammatory and infectious lung diseases http://ow.ly/8YGT302aVlS